Inversion and word order in English: A functional perspective - Aladdin Assaiqeli; Mahendran Maniam; Mohammed Farrah (Studies in English Language and Education, 2021)
English is an SVO (Subject, Verb, Object) word order language. This canonical SVO pattern is the default unmarked word-order configuration typical of English, which makes this language to be classified under the typology of SVO languages. However, driven by the major purpose of language as an instrument of human communication and social interaction, and as a semantic system for making meanings, addressors sometimes depart in their discourse from this basic canonical order of constituents where a grammaticalized system like inversion takes place, resulting in inverted constructions. Through testing and developing the Degree of Focus Hypothesis, proposed by Huffman (1993), this study, which employed a mixed methods research design, sought to explore the communicative and semantic values of inversion; and the pragmalinguistc functions of preposing, i.e., clause-initial adjuncts, to the pragmatic process of communication. The study confirmed the Degree of Focus Hypothesis where the hypothesized notion of concentration of attention stemming from inversion was found to be applicable. The paper stressed that what triggers inversion or non-inversion is a certain communicative effect such as focus rather than a relation of formal determination where one element determines mechanically the form or appearance of another. A contribution to linguistic and educational research, the paper, therefore, highlighted the importance of a human factor in the functioning of language and emphasized the need to break away from grammar-based teaching (traditional grammar) to discourse-based language teaching (communicative grammar) where languaging rather than language should be the focus of language teaching and learning.